2022
DOI: 10.3389/fpsyg.2022.865702
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Online Reviews on Consumers’ Purchasing Decisions: Evidence From an Eye-Tracking Study

Abstract: This study investigated the impact of online product reviews on consumers purchasing decisions by using eye-tracking. The research methodology involved (i) development of a conceptual framework of online product review and purchasing intention through the moderation role of gender and visual attention in comments, and (ii) empirical investigation into the region of interest (ROI) analysis of consumers fixation during the purchase decision process and behavioral analysis. The results showed that consumers’ atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
1
7

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 59 publications
1
34
1
7
Order By: Relevance
“…These reviews play an important role in shaping a product's reputation and influencing other potential buyers. Most importantly, reviews influence the majority of buyers in their purchasing decisions (Chen et al, 2022). Consumers rely on text reviews due to the inadequacy of star ratings.…”
Section: Theoretical Background 21 Rise Of the "Digital Consumer" And...mentioning
confidence: 99%
See 3 more Smart Citations
“…These reviews play an important role in shaping a product's reputation and influencing other potential buyers. Most importantly, reviews influence the majority of buyers in their purchasing decisions (Chen et al, 2022). Consumers rely on text reviews due to the inadequacy of star ratings.…”
Section: Theoretical Background 21 Rise Of the "Digital Consumer" And...mentioning
confidence: 99%
“…The growing influence of reviews goes beyond consumer behaviour and significantly affects the reputation and performance of businesses (Ansary and Nik Hashim, 2018;Rodell et al, 2020). Consumer reviews have a direct impact on purchasing decisions, thus influencing company performance and, in turn, brand reputation (Chen et al, 2022;Fernandes et al, 2022). As a result, companies are recognising the importance of analysing online data, including social media and reviews, as part of their business intelligence efforts.…”
Section: User-generated Content Decision Science and Corporate Perfor...mentioning
confidence: 99%
See 2 more Smart Citations
“…Cautionary feedback could be particularly influential for potential buyers. Clearnet marketplace research has found that individuals who are buying goods are more likely to pay closer attention to negative comments than positive comments when purchasing a product (Chen et al., 2022). This suggests that detailed feedback cautioning future buyers of the potential risks of substances could be particularly influential for buyers to avoid and mitigate the risks of substance use highlighting the importance of feedback as an informative data source for understanding harm reduction strategies.…”
Section: Present Studymentioning
confidence: 99%